RANCANG BANGUN UNMANNED GROUND VEHICLE (UGV) DENGAN MODEL DIFFRENSIAL STEERING BERBASIS GLOBAL POSITIONING SYSTEM (GPS) - Albanna, Reza Alauddin; Widyantara, Helmy; Susanto, Pauladie (Journal of Control and Network Systems, 2014)
The technology which is rapidly developing nowadays is Autopilot Technology. Autopilot technology can be divided into 3 parts: Unmanned Aerial Vehicle (UAV), Remotely Operated Underwater Vehicle (ROUV), Unmanned Ground Vehicle (UGV). UGV is unmanned terrestrial robot, based on how it works UGV can be divided into 2 teleoprated and autonomous. Teleoprated is a vehicle that is controlled by a human operator at a remote location through a communication link. Are autonomous robots that can move automatically which is usually enabled for military purposes.In this final project UGV is design to automatically move toward the point of a pre-determined location. GPS module gives the starting position in the form of longitude and latitude to the microcontroller which then processed by microcontroller and sent to the computer to determine the initial position of UGV. Furthermore, the computer will assign the input in the form of values of X and Y to be addressed by the UGV. This value will be sent to the microcontroller in order to get the angle and distance of the target to be reached by the UGV. Additionally UGV design goal is as the foundation to create a UGV that can function well and furthermore can be developed more perfectly and beneficial for the common good.The digital compass module can able to know the level of accuracy of digital compass CMPS10 with reference to the mobile smartphone with an average error of 6.64. PMB-688 GPS module has been able to determine the level of accuracy of the coordinates of latitude and longitude on moving objects using the reference GPS mobile smartphone with an average error 0.0001175 longitude and latitude average error of 0.00003375.UGV system has been able to move automatically well and can go to the location point that determined with fairly good accuracy with an average error for the angle and distance of 9.071 at 36.21.